Use of mediate implant to replace a dental element with root resorption in the aesthetic area: Case report (Research, Society and Development, 2020)
Currently the use of implants represents an excellent alternative in functional and aesthetic rehabilitation for dentistry. Therefore, the objective of the present study is to report a clinical case on the use of a mediate implant to replace a dental element with root resorption in the aesthetic area. Male patient, 18 years old, sought dental care complaining of bleeding during brushing and dissatisfaction with the smile aesthetic. In the intra-oral clinical examination, it was observed that unit 11 had retraction in the gingival tissues. In addition, the panoramic radiographic examination showed the presence of corono-radicular resorption of the respective dental unit. The treatment plan included three surgical stages, including minimally traumatic extraction of element 11 and soft and hard tissue grafts. It was concluded that the use of the surgical protocol showed excellent aesthetic and functional results, improving the patient's psychosocial aspect. It is important to emphasize that a correct planning of the extraction area must be made, which will be rehabilitated with an implant, in order to obtain a good long-term prognosis.